2014
DOI: 10.1107/s2053230x14014046
|View full text |Cite
|
Sign up to set email alerts
|

Structure ofSaccharomyces cerevisiaemitochondrial Qri7 in complex with AMP

Abstract: N6-Threonylcarbamoyladenosine (t6A) is a modified tRNA base required for accuracy in translation. Qri7 is localized in yeast mitochondria and is involved in t6A biosynthesis. In t6A biosynthesis, threonylcarbamoyl-adenylate (TCA) is synthesized from threonine, bicarbonate and ATP, and the threonyl-carbamoyl group is transferred to adenine 37 of tRNA by Qri7. Qri7 alone is sufficient to catalyze the second step of the reaction, whereas the Qri7 homologues YgjD (in bacteria) and Kae1 (in archaea and eukaryotes) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…developed a non-hydrolysable TC-AMP analogue (termed BK951) and reported its structure bound to the E. coli TsaD-TsaB heterodimer ( 84 ). The structure revealed that the adenine base portion of TC-AMP is ‘sandwiched’ between subdomain 2 and Kae1 specific insert I, similar to the nucleotide binding mechanism of Kae1 enzymes reported in previous structures ( 8 , 84 , 91 , 95 , 105 ). A cation bound by the metal binding triad serves to coordinate the carboxylate group of the threonine moiety of TC-AMP (Figure 3B ).…”
Section: How Keops Functions To Modify Trnasupporting
confidence: 82%
“…developed a non-hydrolysable TC-AMP analogue (termed BK951) and reported its structure bound to the E. coli TsaD-TsaB heterodimer ( 84 ). The structure revealed that the adenine base portion of TC-AMP is ‘sandwiched’ between subdomain 2 and Kae1 specific insert I, similar to the nucleotide binding mechanism of Kae1 enzymes reported in previous structures ( 8 , 84 , 91 , 95 , 105 ). A cation bound by the metal binding triad serves to coordinate the carboxylate group of the threonine moiety of TC-AMP (Figure 3B ).…”
Section: How Keops Functions To Modify Trnasupporting
confidence: 82%
“…Interestingly, the yeast mitochondrial YgjD/Kae1 paralog, Qri7, is capable of the in vitro biosynthesis of tRNA t 6 A on its own if provided with TCA ( 12 , 22 ). The active site of YgjD/Kae1/Qri7 is characterized by a conserved metal-cluster that is contacting the phosphate moieties of a bound ATP ( 23 25 ). Mutations of this metal-binding motif abolish the biosynthesis of t 6 A ( 12 , 13 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…2), 30,31 YrdC and YgjD failed to produce t 6 A in vitro with transcript or t 6 A-deficient tRNA purified from yeast sua5D, 30 suggesting that the biosynthetic machinery for t 6 A biosynthesis required more than these 2 proteins. Over the last 2 years, a flurry of papers have reported the identification of these missing proteins, and elucidated the complete bacterial, 28,33 eukaryotic/archaeal, 29,40-42 and mitochondrial 32,43,44 biosynthetic pathways to t 6 A.…”
mentioning
confidence: 99%